Cerebrovascular Accident Complicating Diabetic Ketoacidosis in a Nigerian Adolescent: A Case Report and Review of the Literature - Akinola IJ; Akinyosoye G; Adedokun SA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Cerebrovascular accident (CVA) is a rare neurological complication of diabetic ketoacidosis (DKA) in the paediatric population. The risk of developing CVA in DKA patients is often increased due to abnormalities in coagulation factors, platelet activation, blood volume and flow, and vascular reactivity. Cerebral oedema, the most common neurological complication of DKA, may also predispose to CVA. We report the case of a -12-year-old adolescent with DKA complicated by CVA. She developed features of right hemispheric CVA while on admission and had radiological confirmation of an ischaemic CVA. This report highlights that cerebrovascular accidents in DKA can easily be missed or confused with cerebral oedema.